Role of sensitizers in imparting the selective response of SnO2/RGO based nanohybrids towards H2S, NO2 and H2. (January 2020) - Bhangare, Bhagyashri; Ramgir, Niranjan S.; Pathak, Ankita; Sinju, K.R.; Debnath, A.K.; Jagtap, S.; Suzuki, N.; Muthe, K.P.; Terashima, C.; Aswal, D.K.; Gosavi, S.W.; Fujishima, A.
Abstract: Excellent electrical and sensing properties of reduced graphene oxide (RGO) and SnO2 have enabled fabrication of nanohybrid sensor with improved response characteristics. Nanohybrids of these two materials harnessing the advantages of the individual components thereby enables tailor made sensors for specific target gases. In the present work, using metal and metal oxide sensitizers, the response of the RGO nanohybrids was systematically tailored towards H2 S, NO2 and H2 gases. Pristine SnO2 /RGO nanohybrids demonstrated a highly sensitive and selective response towards H2 S. It exhibited a sensor response of 3.7 towards 40 ppm of H2 S at 200 °C. Incorporation of Pt and Pd into the nanohybrid matrix has resulted in an enhanced and selective response towards H2 and NO2, respectively. The maximum response of 124 and 49 were obtained towards 2 and 1.6% ofNO2 and H2, respectively. The lowest detection limits were 0.2%, 0.4 and 1 ppm for H2, NO2 and H2 S, respectively.